PERLAKUAN AKUNTANSI ATAS KONSTRUKSI DALAM PENGERJAAN PADA LAPORAN KEUANGAN PEMERINTAH DAERAH PADA KABUPATEN MINAHASA - Siregar, Maruli Harry; Saerang, David P. E. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2015)
This study aimed to assess and provide feedback on the accounting treatment of Construction in Progress which is within the financial statements of Local Government. The analysis method used in this research is to use descriptive analysis method to describes the results of the analysis of the accounting treatment conducted by local government to account Construction in progress. Construction in progress are fixed assets that are in the process of development. The work includes the construction in the land, equipment and machinery, buildings and buildings, roads, irrigation and networks, and other fixed assets that the process of acquisition and / or construction requires a certain period of time and has not been completed. Listing of construction in progress in Minahasa regency government is done by making an adjustment to the journal reported assets unfinished for later recorded under construction in progress. In the process of recording still no records of advances in the development of an asset. There are some problems that can be encountered by the relevant local government recognition of a construction in progress. Recognition of construction in progress are important things that need to follow the guidelines in the Government Accounting Standards. Above special cases should be given special treatment and separate accounting policies in recognition of Construction in progress.